Effect of soybean oil availabilities on rumen biohydrogenation and duodenal flow of fatty acids in beef cattle fed a diet with crude glycerine - Gomez-Insuasti, Arturo Samuel [UNESP]; Granja-Salcedo, Yury Tatiana [UNESP]; Rossi, Luis Gustavo [UNESP]; Ramalho Vieira, Bruno [UNESP]; Berchielli, Telma Teresinha [UNESP] (Taylor & Francis, 2018)
Soybean oil with different ruminal availability (whole soybeans (WS), soybean oil (SO) and calcium salts (CS)) was used to evaluate the fatty acid (FA) intake, rumen biohydrogenation (BH) and duodenal flow of FA in Nellore steers fed diets with crude glycerine (CG). Eight castrated Nellore steers were fitted with a ruminal and duodenal silicone cannula, and distributed in a double, simultaneous, Latin square 4 × 4 design with four diets and four experimental periods. Concentrates contained ground maize, urea, mineral salts, CG (100 g/kg DM) and soybean products with different availability of soybean oil: (1) no additional fat (CO), (2) WS, (3) SO or (4) CS. Fat supplementation was fixed to obtain 50 g ether extract/kg DM. Experimental treatments had no effect on DM intake, DM duodenal flow or ruminal turnover rate of C:16 FA. However, fat addition increased C:18 and turnover rates of total FA rumen (p < 0.05). CS resulted in lower C:18 turnover rates and lower ruminal BH of monounsaturated and unsaturated FA (UFA) than WS (p < 0.05). SO resulted in a greater duodenal flow of C18:0 (stearic acid), C18:1t-11 (vaccenic acid) and saturated FA than the WS and CS diets (p < 0.05). CS resulted in a higher duodenal flow of C18:3n-3 (linolenic acid) than WS (p < 0.05). The association of CG and calcium salts in Nellore steers was the best nutritional strategy to increase duodenal flow of healthier UFA, which may increase the deposition of these FA in meat. However, SO associated with CG association increased the duodenal flow of vaccenic acid, which is main precursor of endogenous synthesis of conjugated linoleic acids in tissues.
Keywords: Beef cattle; conjugated linoleic acid; glycerol; lipid metabolism; protected fat